Avaliação in-vitro da atividade antifúngica e da citotoxicidade da própolis de copaíba contra espécies do gênero Candida spp - Henrique Cortes Meira (2017)
OBJECTIVES: verify the antifungal activity and cytotoxicity of copaiba propolis and its mouthwash prototype against Candida spp. METHODOLOGY: the chromatographic profile of the propolis extract was performed by Reverse Phase Ultra-efficiency Liquid Chromatography (RP-UPLC). The antifungal activity of copaíba propolis extract (CPE) andits mouthwash prototype against C. albicans, C. tropicalis and C. krusei was evaluated by microdilution broth method and agar disk-diffusion. Cytotoxicity was verified by the MTT assay on 3T3-L1 fibroblasts. RESULTS: Phenols were the main compounds found, among them caffeic acid (phenolic acid) and canferol (flavonoid). The MIC values were 156 g/ml, 312 g/ml and 625 g/ml for C. albicans, C. tropicalis and C. krusei respectively, indicating present but moderate antifungal activity. The values of the inhibition zones suggested a fungistatic activity of the oral rinse. In relation to cytotoxicity tests, CPE exerts a dosedependent effect on the 3T3-L1 fibroblasts proliferation at low concentrations and may exert a tissue regenerative effect. CONCLUSIONS: the investigated propolis has a moderate antifungal potential against Candida spp., and mouthwash may be a therapeutic option in the fight against oral candidiasis, since its treatment is based on control and not on the eradication of yeast. Future studies on the characterization of its chemical compounds, product enhancement and clinical trials should be performed.